Oil sands development: a health risk worth taking? - Tenenbaum, D. J. (Environmental Health Perspectives, 2009)
As traditional petroleum supplies dwindled and prices soared over the past few years, oil companies have shifted their attention to oil sands, a mix of sand, water, and a heavy, viscous hydrocarbon called bitumen that can be converted to oil. With the plunge in oil prices in fall 2008, many producers began canceling or postponing plans to expand oil sands development projects, but this turn of events could yet reverse, as Canada's vast oil sands deposits are lauded as a secure source of imported oil for the United States. At the same time, however, oil sands present troubling questions in terms of the environmental health effects associated with their development.
Keywords: arsenic; birds; bitumen; cancer; First Nations; George Poitras; health; mercury; Mikisew Cree First Nation; moose; tailings; tailings ponds; traditional diets; walleye; whitefish